Persepsi Pedagang Kaki Lima Terhadap Satpol PP Perempuan di Kota Payakumbuh - Dhini Hariani; Ikhwan Ikhwan (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This research is motivated by the renewal of the recruitment of members of the Civil Service Police Unit (Satpol PP), this regional apparatus opens opportunities and opportunities for women to join one of the tasks, namely Controlling Street Vendors (PKL) which often causes conflicts, clashes and resistance. The purpose of this study is to explain how the perception of the street vendors towards the tasks carried out by the Women's Civil Service Police Unit on Jalan Ahmad Yani, Pasar Ibuh, Payakumbuh. In this study, it was studied using Alfred Schutz's phenomenological theory. The research method used in this study is a qualitative approach with the type of case study. The informant selection technique in this study used a purposive sampling technique with 15 informants. Data collection techniques used in this study are observation, interviews and documentation. The data triangulation used is technique triangulation and source triangulation. The data were analyzed by using Mathew Milles and Huberman analysis techniques with data reduction process, data presentation and conclusion drawing. The results of this study indicate that there are several perceptions of the PKL community towards the implementation of the tasks carried out by the Women's Satpol PP which can be seen from several elements, namely: 1) the PKL community perception of the control activities carried out by the female Satpol PP 2) the PKL community perception of the procedure. policing carried out by female Satpol PP 3) community perception of street vendors of the communication process in policing carried out by female Satpol PP.